The Role of Awareness Guidance in Integrating the Competency-Based Approach Strategy: An Applied Study from the Perspective of Workers in Jordanian, Saudi and Emirati Universities - Mahfoudh, Naoufel; Rshaid, Abdullah M. Bani; Ali, Manal ElSayed Ahmed; Snoussi, Thouraya; Abduljabbar, Omer Jawad; Darawsheh, Saddam Rateb; Al-lawama, Haron ismail (Journal of Posthumanism, 2025)
The aim of the study is to examine the relationships between approach strategy competencies, cultural adaptation, implementation challenges, and perceived effectiveness of mentoring interventions. The study population consists of academics in Jordan, Saudi Arabia, and the UAE, with a sample size of 60 academics from three universities in the countries, namely Jordan, Saudi Arabia, and the UAE, and 200 male and female students. The sample was conducted using stratified random sampling, ensuring representation from different universities in the three countries. Methodologically, the study used partial least squares (PLS) regression analysis and analysis of variance to analyze the data collected through surveys and interviews. The results indicate a significant positive relationship between approach strategy competencies and cultural adaptation with perceived effectiveness, while implementation challenges showed marginal significance. Based on these findings, recommendations include investing in academics’ professional development, enhancing cultural competence, allocating adequate resources, promoting collaboration, implementing data-driven practices, addressing systemic barriers, promoting self-care among mentors, and continually evaluating and adapting mentoring programs. These recommendations aim to improve the effectiveness of counseling interventions and support student well-being in universities in the three countries.